2022
DOI: 10.1002/mlf2.12045
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficiency genome editing of an extreme thermophile Thermus thermophilus using endogenous type I and type III CRISPR‐Cas systems

Abstract: Thermus thermophilus is an attractive species in the bioindustry due to its valuable natural products, abundant thermophilic enzymes, and promising fermentation capacities. However, efficient and versatile genome editing tools are not available for this species. In this study, we developed an efficient genome editing tool for T. thermophilus HB27 based on its endogenous type I-B, I-C, and III-A/B CRISPR-Cas systems. First, we systematically characterized the DNA interference capabilities of the different types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…1 d and e). Considering the widespread utilization of endogenous or heterogenous type I and II systems in thermophiles [ 16 , 20 , [34] , [35] , [36] ], our discoveries provide essential components for developing extensive range genomic deletion tools or donor DNA-free gene knockout tools in other biotechnological potential thermophilic strains [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 d and e). Considering the widespread utilization of endogenous or heterogenous type I and II systems in thermophiles [ 16 , 20 , [34] , [35] , [36] ], our discoveries provide essential components for developing extensive range genomic deletion tools or donor DNA-free gene knockout tools in other biotechnological potential thermophilic strains [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As it currently stands, there is a lack of broadly applicable genetic tools, including selectable markers, promoters, plasmid origins, and transformation protocols, as broadly utilized mesophilic tools are not functional in these thermophilic microbes (Y. Wang et al., 2024 ; Ye et al., 2023 ). While there are a growing number of tools being generated for use in thermophilic microbes (Adalsteinsson et al., 2021 ; Le & Sun, 2022 ; Riley et al., 2019 ; Walker et al., 2020 ; Wang et al., 2022 ; Wu et al., 2023 ; Yang et al., 2023 ), developing new tools and implementing CRISPR mediated genome engineering and/or thermostable serine recombinase-assisted genome engineering (SAGE) mediated integration would greatly simplify testing production of various industrial chemicals in these currently underutilized microbes (Fenster & Eckert, 2021 ; Wu et al., 2023 ). Continued decrease in -omics costs coupled with advanced genome modification techniques makes adopting extremophiles and other novel, less studied microbes as industrial chassis a viable and exciting avenue of research that should be more intensely pursued.…”
Section: Discussionmentioning
confidence: 99%
“…They relieve the effects of environmental stressors by controlling the distribution of nutrients, moving them to their intended destination. Their most notable qualities are a lower need for synthetic fertilizers, higher yields with less time and effort, lower environmental impacts, lower costs, and more nutrient availability and absorption [ 18 ]. It was shown that NPs can affect plant–microbe interactions in two ways: directly, by altering the accessibility to nutrients in the rhizospheric soil, and indirectly, by stimulating microorganisms.…”
Section: Agriculture In the 21st Centurymentioning
confidence: 99%